Orbital Swelling and Ptosis as an Initial Presentation of Childhood Acute Lymphoblastic Leukaemia: A Case Report and Review of the Literature - Ahmed Alsalem; Bayan Almasoudi; Ghaida Alzahrani; Lama Sindi; Joud Alwan (Case Reports in Pediatrics)
We are reporting the case of a 3-year-old-girl who initially presented with unilateral eyelid swelling and ptosis. A diagnosis of acute lymphoblastic leukaemia (ALL) was eventually made based on an orbital incisional biopsy and a bone marrow examination. Historically, orbital involvement had been linked to myeloid leukaemia; however, in lymphoid leukaemia, they are increasingly being implicated and had been reported as the sole presentation of the disease. These findings stress the importance of conducting ophthalmologic assessments in cases diagnosed with ALL in order to prevent delays in proper assessment and treatment. Management options in orbital disease are fortunately not significantly different than well-established treatment protocols.